Understanding Women’s Perceptions of Promoting Education and Policy Initiatives about Climate Change in Rural Areas of Sindh, Pakistan - Memon, Falak Shad (Social Science Research Network, 2020)
Climate change is an inevitable issue of modern world. Women often face greater risk and share greater burden due to their limited adaptive capacity. Studies suggest that knowledge and education can result in better resilience and sustainable development. Climate change education encourages changes in attitude and behavior that leads to better adaptability to climate changes. This paper aims to explore the local women’s understanding of climate change education and policy initiatives taken in rural areas. A qualitative exploratory study was chosen for this study. The data collection methodology was through qualitative process. 20 women participants from rural areas of Sindh were interviewed. The finding reveled that women in rural area of Sindh have very low understanding and knowledge of any climate change educational program conducted in their regions. The lack of awareness regarding any climate change policy initiatives was also observed. This lack of awareness was attributed to their low literacy rate, lack of gender inclusiveness and cultural barriers and hindrances. The understanding of these factors at all level of policy making is key for successful climate change education policy.
openalex: W3179999768 mag: 3179999768
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:yes; ⛔ No DOI found